2022
DOI: 10.1186/s12915-022-01387-z
|View full text |Cite
|
Sign up to set email alerts
|

Receptor deorphanization in an echinoderm reveals kisspeptin evolution and relationship with SALMFamide neuropeptides

Abstract: Background Kisspeptins are neuropeptides that regulate reproductive maturation in mammals via G-protein-coupled receptor-mediated stimulation of gonadotropin-releasing hormone secretion from the hypothalamus. Phylogenetic analysis of kisspeptin-type receptors indicates that this neuropeptide signaling system originated in a common ancestor of the Bilateria, but little is known about kisspeptin signaling in invertebrates. Results Contrasting with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…The occurrence of kisspeptin-type precursors in echinoderms was first reported with the identification of a protein in A. rubens (ArKPP), which comprises two kisspeptin-like peptides ( Semmens et al, 2016 ), and orthologs of this protein have been identified in other echinoderms ( Zandawala et al, 2017 ; Chen et al, 2019 ). Recently, a second kisspeptin-type precursor, also comprising two kisspeptin-like peptides, was identified in A. rubens and other echinoderms ( Escudero Castelán et al, 2022 ). Therefore, these two precursor types are now referred to as KPP1 and KPP2, respectively, and here we report their identification in crinoids.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The occurrence of kisspeptin-type precursors in echinoderms was first reported with the identification of a protein in A. rubens (ArKPP), which comprises two kisspeptin-like peptides ( Semmens et al, 2016 ), and orthologs of this protein have been identified in other echinoderms ( Zandawala et al, 2017 ; Chen et al, 2019 ). Recently, a second kisspeptin-type precursor, also comprising two kisspeptin-like peptides, was identified in A. rubens and other echinoderms ( Escudero Castelán et al, 2022 ). Therefore, these two precursor types are now referred to as KPP1 and KPP2, respectively, and here we report their identification in crinoids.…”
Section: Resultsmentioning
confidence: 99%
“…The A. mediterranea kisspeptin-type precursor 1 (AmKPP1) is a 189-residue protein that comprises two putative kisspeptin-like peptides (AmKP1.1, AmKP1.2), both of which are predicted to be C-terminally amidated ( Figure 2C ). Accordingly, kisspeptin-type precursors in eleutherozoans also comprise two putative C-terminally amidated kisspeptin-type peptides (e.g., ArKP1.1 and ArKP1.2 in A. rubens ; Semmens et al, 2016 ; Escudero Castelán et al, 2022 ). Alignment of crinoid KP1.1-type peptides with eleutherozoan KP1.1-type peptides revealed a conserved C-terminal Arg-X-Leu-Pro-Phe-NH 2 (RXLPFamide, where X is variable) motif and a conserved Asn (N) residue in the core of the peptide sequences ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations